(3GdGOGQI dQLGd GdGYeGd h GdMcheGJ (B/s - (3edhNjI, GMeO ahRjs ((3GdGScfOQjI(B: s (3OGQ GdacQ GdLGeYj(B, s, 2007)
(3jYQV gPG GdcJGH GdaUd GdGhd (B: (3GSGSjGJ GdGOGQI GdYGeI (B: (3GhdG (B: (3GSHGH OQGSI GdGOGQI(B- (3GdaUd GdKGfi (B: (3GdeOGNd GdeYGUQI dOQGSI GdGOGQI GdYGeI (B: (3ChdG (B: (3GdeONd GdbGfhfi (B: (3KGfjG (B: (3GdeONd GdhUai (B((3Gh GdTcdi(B)- (3GdaUd GdKGdK (B: (3GdeOjQjhf (B: (3hXGFage heeGQSJge (B: (3JYQja GdeOjQ(B-(3GdaUd GdQGHY (B: (3GdLgGR GdGOGQi ddOhdI (B: (3GhdG (B: (3GdGgOGa GdYGeI (B: (3KGfjG (B: (3JUfja GdefXeGJ GdYGeI(B- (3GdaUd GdNGeS (B: (3GdHjQhbQGWjI (B: (3GhdG (B: (3fXQjI eGcS ajQ ai GdHjQhbQGWjI (B: (3KGfjG (B: (3GdGWGQ GdacQi ddHjQhbQGWjI(B- (3GdaUd GdSGOS (B: (3GdOhdI hGdMcheI (B: (3GhdG (B: (3eaghe GdOhdI (B: (3KGfjG (B: (3CQcGf GdOhdI(B- (3GdaUd GdSGHY (B: (3GdHjFI GdSjGSjI (B: (3GhdG (B: (3fhY GdOhdI (B: (3KGfjG (B: (3fXGe GdMce(B- (3GdaUd GdKGef (B: (3GdHjFI GdGLJeGYjI (B: (3GhdG (B: (3GdHfGA GdGLJeGYi (B: (3KGfjG (B: (3GdJQcjH GdJYdjej hGdKbGaj(B- (3GdaUd GdJGSY (B: (3GdHjFI GdGbJUGOjI (B: (3GhdG (B: (3JQcjH Gdgjcd GdGbJUGOi (B: (3KGfjG (B: (3eSJhi GdJbOe GdGbJUGOj(B-(3GdaUd GdYGTQ (B: (3GdSdWI (B: (3GhdG (B: (3eaghe GdSdWI (B: (3GdaUd GdMGOi YTQ (B: (3GdeSFhdjI GdYGeI(B- (3GdaUd GdKGfi YTQ (B: (3GdeQcRjI hGddGeQcRjI(B- (3GdaUd GdKGdK YTQ (B: (3GJNGP GdbQGQGJ(B- (3GdaUd GdQGHY YTQ (B: (3GdGOGQI GdeMdjI(B- (3GdaUd GdNGeS YTQ (B: (3GJLGgGJ hJMOjGJ GdGYeGd ai GdbQf GdMGOi hGdYTQjf hcjajI ehGLgJgG(B.s
(3HjHdjhZQGajG U(B.255 s
Keywords: (3EOGQI GdGYeGds; (3QLGd GdCYeGds